The role of information in transit use by undergraduate and graduate students in Brazil and Denmark - MONTEIRO, Mayara Moraes (2016)
With the fast improvement of technology, accompanied by changes in the lifestyle and the growth of cities, that made the Public Transport (PT) system more complex, delivery of integrated information on PT systems in an efficient and clear way are of the outmost importance but not always available. This study sought to understand the relation between travel information, PT use intentions and non-habitual travel (at night). The hypothesis is that PT use intentions are related to the perceived usefulness and the ease-of-use of the system, which are related to information quality and real-time information availability. The hypothesized relations are anchored theoretically in the Extended Technology Acceptance Model and validated empirically in two sources of data: (i) Copenhagen (Denmark), characterized by a highly integrated PT system with an advanced web-based information system; (ii) Recife and Natal (Brazil), characterized by a lower perceived Level Of Service (LOS) and non-integrated information sources. The data was collected through a tailor-made survey answered for 1,123 university students in Denmark and Brazil. Structural equation models were employed for explaining the use of PT as a function of the observed respondent characteristics and the latent constructs. The results show: (i) information quality is essential for explaining PT use; (ii) perceived information quality is directly and positively related to perceived LOS, convenience and familiarity with the PT system; (iii) the use of real-time information is positively related to information quality and familiarity, while it is negatively associated with perceived PT security; (iv) PT use at night is positively related to habitual PT use and information search